The profiling of car design product using Bezier curve for customer product design preferences - Wan Yaacob, Wan Nur Hidayah (2021)
This research discussed about the characteristics of product design based on customer emotions using the ‘Kansei Engineering’, ‘Kansei Words’, and ‘mathematical approach’. Customers emotion are important in determined the product will successful in the market. However, it was difficult to interpreted customers emotion into verbal. The aims of this research are to identify and analyze the emotional product based on the customer preferences compared to the image of the product. The main survey is distributed to 220 students at Universiti Teknikal Malaysia Melaka. There are two categories of the car design used in the questionnaire of investigating the car design preferences towards the Kansei Words. 5 Kansei Words showed the semantic articulated the customer emotional design towards the cars such as ‘stylish’, ‘comfortable’, ‘sporty’, ‘safety’, and ‘elegant’. Statistical Package for the Social Sciences (SPSS) is used to analyze the respondent’s answers for statistical data. On this research, twenty cars in each category applied Bezier curves (Geogebra) including the segmentation of the design profile. The ranges in each category are identified from the value in Geogebra. After completing the preliminary test, there are only six cars for each category are selected. In the main survey using six cars in the questionnaire, there are only three cars are selected based on the respondents’ preferences. For the Kansei preferences, the higher average of Kansei Words is determined. The most preferable Kansei Words of city car for front view and rear view was safety and side view result is stylish. For sedan car, the preferable Kansei Word for all view of sedan car was stylish. 3 preference car for city car front view was Toyota Etios Liva, Peugeot 108 and Toyota Aygo. Then for rear view was Peugeot 108, Toyota Etios Liva, and Toyota Aygo. While for side view, 3 car preference was Peugeot 108, Chevrolet Spark and VW Polo. 3 preference car for sedan car front view was BMW f80, Hyundai Sonata and Mercedes E class. Then for rear view was BMW f80, Mercedes E class, and Mitsubishi Lancer. While for side view, 3 car preference was Aston Martin, BMW f80 and Mercedes E class. Bezier curve 1 and 2 has high correlation in front view city car. While for rear view and side view, the high correlation occurs in Bezier curve 5. Sedan car front view has high correlation in Bezier curve 8. Then for rear view was Bezier curve 4 and for side view Bezier curve 3.